Atlas of Honduras: Mitch Data - Barona, Elizabeth; Barreto, Hector; Couillaud, Patrice; Cox, Julie; Leclerc, Gregoire; Jiménez, Pedro; Urbano, Paloma; Lamy, France; Nelson, Andy; Farrow, Andrew (2021)
The main objective of this project is the creation of a system that integrates biophysical and socioeconomic information at different scales in order to perform analyses at various administrative levels.